1999
DOI: 10.1126/science.285.5434.1716
|View full text |Cite
|
Sign up to set email alerts
|

An Infrared Spectral Match Between GEMS and Interstellar Grains

Abstract: Infrared spectral properties of silicate grains in interplanetary dust particles (IDPs) were compared with those of astronomical silicates. The approximately 10-micrometer silicon-oxygen stretch bands of IDPs containing enstatite (MgSiO3), forsterite (Mg2SiO4), and glass with embedded metal and sulfides (GEMS) exhibit fine structure and bandwidths similar to those of solar system comets and some pre-main sequence Herbig Ae/Be stars. Some GEMS exhibit a broad, featureless silicon-oxygen stretch band similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(146 citation statements)
references
References 40 publications
7
139
0
Order By: Relevance
“…This raises the question: is the chemical composition of ISM grains that we have derived consistent with that of GEMS? The idea that GEMS are unprocessed interstellar grains is supported by a similarity between the shape of the 10 µm feature of some GEMS and that observed for the interstellar medium (Bradley et al 1999b), although also distinct differences can be identified (Bradley et al 1998). In addition, traces of exposure of GEMS to ionizing radiation consistent with an interstellar origin have been reported (Bradley 1994).…”
Section: The Nature Of Gemsmentioning
confidence: 89%
See 1 more Smart Citation
“…This raises the question: is the chemical composition of ISM grains that we have derived consistent with that of GEMS? The idea that GEMS are unprocessed interstellar grains is supported by a similarity between the shape of the 10 µm feature of some GEMS and that observed for the interstellar medium (Bradley et al 1999b), although also distinct differences can be identified (Bradley et al 1998). In addition, traces of exposure of GEMS to ionizing radiation consistent with an interstellar origin have been reported (Bradley 1994).…”
Section: The Nature Of Gemsmentioning
confidence: 89%
“…It has been suggested that GEMS (Glass with Embedded Metal and Sulphides), which are small subgrains found in many IDPs, are unprocessed interstellar dust grains (Bradley et al 1999b). This raises the question: is the chemical composition of ISM grains that we have derived consistent with that of GEMS?…”
Section: The Nature Of Gemsmentioning
confidence: 99%
“…The study of anhydrous IDPs has given us a picture of the material from which the solid components of comets are composed : primary silicates (predominantly the orthopyroxene, enstatite, but olivine and clinopyroxenes do occur), organics and glass with embedded metal and sulphides (GEMS). This last component is thought to be original interstellar material (Bradley 1994;Bradley et al 1999). Visible reflectance spectroscopy has been applied to IDPs, in order to compare them with primitive meteorites and with astronomical data (Bradley et al 1996).…”
Section: Meteorites and Interplanetary Dust Particlesmentioning
confidence: 99%
“…Tiny submicrometer spheroids are likely either solar nebula or presolar interstellar grains [6]. In addition, IDP isotopic anomalies of H, N, O indicate a presolar or interstellar origin.…”
Section: Interplanetary Dustmentioning
confidence: 99%
“…6 An example of impact sensor with PZT's developed for GIADA. The system is open to show the positioning of the piezoelectric sensors below the aluminium sensing plate specific configurations [11][12][13], a minimum momentum of 6.5 × 10 −10 kg m s −1 can be detected.…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%